(3GdMUGfI GdbVGFjI hGdMUGfI GdJfajPjI GdeYJQa HgG ddCTNGU GdGYJHGQjI GdOhdjI, GdOhd hGdefXeGJ hGdgjFGJ GdOhdjI hdCYVGFgG GdeYJeOjf, (B((3GdQDSGA hGdeeKdjf GdOHdheGSjjf(B) (3CeGe GdbVGA GdCLfHj hbVGA GdJMcje (B:s "(3CSGSgG, hfWGbgG, eGgjI GdOaY HgG, hWHjYJg, hGfJgGFgG(B" : (3OQGSI JCUjdjI JMdjdjI JWHjbjI ebGQfI (B/s - (3GdJMjhj, eMehO GdSjO YeQs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2011)
(3jJfGhd cJGH GdMUGfI GdbVGFjI hGdMUGfI GdJfajPjI GdeYJQa HgG ddCTNGU GdGYJHGQjI GdOhdjI, GdOhd hGdefXeGJ hGdgjFGJ GdOhdjI hdCYVGFgG GdeYJeOjf, (B((3GdQDSGA hGdeeKdjf GdOHdheGSjjf(B) (3CeGe GdbVGA GdCLfHj hbVGA GdJMcje CSGSgG, hfWGbgG, eGgjI GdOaY HgG, hWHjYJg, hGfJgGFgG(B: (3OQGSI JCUjdjI JMdjdjI JWHjbjI ebGQfI GdHGH GdChd (B: (3eGgjI GdMUGfI GdbVGFjI ddCTNGU GdGYJHGQjI GdOhdjI hCYVGFgG GdeYJeOjf CeGe GdbVGA GdCLfHj hbVGA GdJMcje CSGSgG hfWGbgG (B(2013) (3GdHGH GdKGfj (B: (3eGgjI GdOaY HGdMUGfI GdbVGFjI (B(2013) (3GdHGH GdKGdK (B: (3CYeGd GdOaY HGdMUGfI GdbVGFjI (B(2013) (3GdHGH GdQGHY (B: (3CYeGd GdOaY HGdMUGfI GdbVGFjI CeGe gjFI GdJMcje (B(2013) (3GdHGH GdNGeS (B: (3CYeGd GdOaY HGdMUGfI GdbVGFjI CeGe GdbVGA (B(2013) (3GdHGH GdSGOS (B: (3GfJgGA GdMUGfI GdbVGFjI (B(2013) (3GdHGH GdSGHY (B: (3GdMUGfI GdJfajPjI ddCTNGU GdGYJHGQjI GdOhdjI hCYVGFgG GdeYJeOjf CeGe GdbVGA GdCLfHj hbVGA GdJMcje (B(2013) (3GdHGH GdKGef (B: (3CYeGd GdOaY HGdMUGfI GdJfajPjI ddCTNGU GdGYJHGQjI GdOhdjI hCYVGFgG GdeYJeOjf(B-(3GdHGH GdJGSY (B: (3GfJgGA GdMUGfI VO GdJfajP ddCTNGU GdGYJHGQjI GdOhdjI hCYVGFgG GdeYJeOjf(B.s
(3HHdjhLQGajI (B: (3UaMI (B419.s
Keywords: (3GdMUGfI GdbVGFjI (B((3bGfhf Ohdj(B)s; (3GdMUGfI GdOHdheGSjI (B((3bGfhf Ohdj(B)s